Alternative splicing of MaMYB16L regulates starch degradation in banana fruit during ripening. Issue 7 (27th April 2021) - Jiang, Guoxiang; Zhang, Dandan; Li, Zhiwei; Liang, Hanzhi; Deng, Rufang; Su, Xinguo; Jiang, Yueming; Duan, Xuewu
Abstract: The alternative splicing of select genes is an important mechanism to regulate responses to endogenous and environmental signals in plants. However, the role of alternative splicing in regulating fruit ripening remains unclear. Here, we discovered that MaMYB16L, an R1‐type MYB transcription factor, undergoes alternative splicing and generates two transcripts, the full‐length isoform MaMYB16L and a truncated form MaMYB16S, in banana fruit. During banana fruit ripening, the alternative splicing process intensifies with downregulated MaMYB16L and upregulated MaMYB16S . Moreover, MaMYB16L is a transcriptional repressor that directly binds with the promoters of many genes associated with starch degradation and MaDREB2, a positive ripening regulator, and represses their expression. In contrast, MaMBY16S lacks a DNA‐binding domain but competitively combines and forms non‐functional heterodimers with functional MaMYB16L. MaMYB16L‐MaMYB16S heterodimers decrease the binding capacity and transrepression activity of MaMYB16L. The downregulation of MaMYB16L and the upregulation of MaMYB16S, that is, a decreased ratio of active to non‐active isoforms, facilitates the activation of ripening‐related genes and thereby promotes fruit ripening. Furthermore, the transient overexpression of MaMYB16S promotes banana fruit ripening, whereas the overexpression of MaMYB16L delays this process. Therefore, the alternative splicing of MaMYB16L might generate a self‐controlled regulatory loop to regulate banana fruit ripening. Abstract : Alternative splicing of MaMYB16L generates two transcripts, the full‐length isoform MaMYB16L and a truncated splice form MaMYB16S, which form a self‐controlled regulatory loop to regulate banana fruit ripening by regulating the expression of many starch degradation‐related genes and MaDREB2 .